Estimativas da funç\~ao de exportaç\~oes brasileiras agregadas com dados das contas nacionais trimestrais (1995-2009) - Bernardo Patta Schettini; Gabriel Coelho Squeff; Raphael Rocha Gouvêa (Instituto de Pesquisa Econômica Aplicada (IPEA), 2011)
– This paper presents new econometric specifications for the Brazilian exports in the period 1995-2009 using data from the Quarterly Accounts and allowing for nonlinearities. In the cointegrating vector, there is evidence of a level shift, but the elasticities have not changed significantly. The income-elasticity remained close to the unity, and the real exchange rate multiplier was small. In the short-run dynamics, the world income exerts a nonnegligible influence, and the exchange rate is not significant. We estimate the correction of disequilibria occurs within three quarters. In addition, we underscore selected models exhibited a good performance in the outof-sample one-step-ahead forecast.
Keywords: F1; F17; C22; C52; 330; Export; Schätztheorie; Brasilien